Enhancing The Student's Ability In Writing Descriptive Text By Using Pictures At Tenth Grade of SMK Yapis Timika - Fadlan, Azwar; Tanan, Sartin (Jurnal Ilmiah Spectral, 2024)
This research project was enforced based on the outcome of the researchers' observations at SMK Yapis (Yapis Vocational School) Timika, where almost all students experienced difficulties in writing English texts, especially descriptive texts. Based on that problem, the researchers tried to find out a solution by reading several theories from various existing literatures. In the end, the researchers tried to use a medium, namely the use of pictures to enhance students' enthusiasm and encouragement in the learning process of writing descriptive text. This research project was a Class Action Research (CAR) and used two types of instruments, namely tests and observations. To measure the students’ writing ability, the researchers used the components that were adapted from Jacob's assessment rubric. This research project aimed to enhance the students’ writing skills in descriptive text. In this study, the researchers attempted to enhance the way of teaching writing by making use of pictures. It had been held in some cycles to break the problem occurring in teaching and studying writing. The results showed that, apart from increasing students' encouragement and enthusiasm in the class, using pictures as the media was also able to increase students' imagination in developing ideas and concepts for writing descriptive text.